Distribution of Clostridium difficile PCR ribotypes and high proportion of 027 and 176 in some hospitals in four South Eastern European countries. (December 2016) - Rupnik, Maja; Tambic Andrasevic, Arjana; Trajkovska Dokic, Elena; Matas, Ivanka; Jovanovic, Milica; Pasic, Selma; Kocuvan, Aleksander; Janezic, Sandra
Abstract: While Clostridium difficile epidemiology is well documented in many European countries, data are largely missing for South Eastern European region. Here we report the PCR ribotype distribution of 249 C. difficile isolates received for typing from six hospital settings from Croatia, Bosnia and Herzegovina, Republic of Macedonia and Serbia in time period from 2008 to 2015. Twenty-four PCR ribotypes were detected. The majority of strains from Bosnia and Herzegovina and Serbia belonged to PCR ribotype 027 (65.8%). Other three dominating PCR ribotypes were 176 (18 strains; Croatia), 001/072 (15 strains; all countries) and 014/020 (15 strains; all countries). Highlights: Ribotype distribution for C. difficile strains from selected hospitals from four South East European countries is given. In epidemic settings PCR ribotypes 027 and 176 were dominant. In non-epidemic settings PCR ribotypes 001/072 and 014/020 were dominant.